Nursing activities for the diagnosis "Risk for contamination of medical devices" (Research, Society and Development, 2020)
Objective: to seek evidence of consensus among specialists to validate Nursing activities for the diagnosis “Risk for contamination of articles”. Methodology: this is a quantitative, descriptive, methodological study of validity by consensus of experts. It is reported that 35 specialist nurses in the operating room and material and sterilization center participated. An instrument was applied that contained the risk factors of the diagnosis and the activities proposed for them. Activities with more than 90% consensus were considered valid. Results: agreement was observed for 25 activities proposed for 11 risk factors and two risk factors did not obtain an agreement greater than 90% for their activities. Conclusion: there was agreement between the proposed and the validated by the specialists for 25 activities. It is believed that the relevance of the study is in the determination of nursing activities, characterizing care indirectly in the material and sterilization center and the nurse's work in this unit. As a limitation of the study, the need to validate the rejected activities and update the diagnosis title for later validation are pointed out.